Der Investiturstreit in England, by Stefanie Schild - Peltzer, Jörg (The English historical review, 2017)
The Investiture Controversy between pope and emperor at the turn of the eleventh to the twelfth century has been a central issue of German medieval historiograp
Gesehen am 11.07.2018
Keywords: Rezension